2010
DOI: 10.1002/chem.201001520
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Catalyzed Cycloetherification Reactions of β,γ‐ and γ,δ‐Allendiols: Chemo‐, Regio‐, and Stereocontrol in the Synthesis of Oxacycles

Abstract: Versatile routes that lead to a variety of functionalized enantiopure tetrahydrofurans, dihydropyrans, and tetrahydrooxepines are based on chemo-, regio-, and stereocontrolled metal-catalyzed oxycyclization reactions of β,γ- and γ,δ-allendiols, which were readily prepared from (R)-2,3-O-isopropylideneglyceraldehyde. The application of Pd(II), Pt(II), Au(III), or La(III) salts as the catalysts gives controlled access to differently sized oxacycles in enantiopure form. Usually, chemoselective cyclization reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…Since the first report of the palladium(II)-catalyzed cycloisomerization of 1,2-allenyl ketones by an oxypalladation process by Hashmi et al in 1997, [276] palladium(II)catalyzed cyclization/coupling reactions of allenoic acids, amides, allenols, allenic ketones, 1,2-allenyl phosphonic acids, and allenic amines in the presence of allylic halides, [277] or w-1-alkenyl halides, [278] alkenes, [279] alkynes, [280] allenylic alcohols or acetates, [281] allenes, [282] and bisallenes [283] have been established. These transformations allow the synthesis of a variety of different cyclic products, which are commonly observed units in natural products, with high efficiency of chirality transfer by an anti-nucleometalation mechanism (Scheme 110).…”
Section: Cyclization Reactions Initiated By Nucleometalationmentioning
confidence: 99%
“…Since the first report of the palladium(II)-catalyzed cycloisomerization of 1,2-allenyl ketones by an oxypalladation process by Hashmi et al in 1997, [276] palladium(II)catalyzed cyclization/coupling reactions of allenoic acids, amides, allenols, allenic ketones, 1,2-allenyl phosphonic acids, and allenic amines in the presence of allylic halides, [277] or w-1-alkenyl halides, [278] alkenes, [279] alkynes, [280] allenylic alcohols or acetates, [281] allenes, [282] and bisallenes [283] have been established. These transformations allow the synthesis of a variety of different cyclic products, which are commonly observed units in natural products, with high efficiency of chirality transfer by an anti-nucleometalation mechanism (Scheme 110).…”
Section: Cyclization Reactions Initiated By Nucleometalationmentioning
confidence: 99%
“…Appli-cation of La[N(TMS) 2 ] 3 have been tested by Alcaide et al on chiral β,γand γ,δ-allendiols leading to hydroxymethylfurane unlike Pt, Pd and Au salts. 76 In the course of studies, Dzudza and Marks et al have also reported that lanthanide triflates could be associated with ionic liquid (IL) to improve the catalytic efficiency of the functionalisation of alkenes (Scheme 25). 77 ILs have been chosen for their low volatility, their high polarity and their potential environmental benefit.…”
Section: C-o Bond Formationmentioning
confidence: 99%
“…72 This aldehyde was not very stable, but could be trapped in situ by a stabilised Wittig reagent. The mechanism proposed for the formation of the oxidised product goes via the 6-endo oxyplatination of the activated π-complex to form, in the first instance the expected 25 (dihydropyranyl)methanol derivative.…”
Section: Scheme 64mentioning
confidence: 99%